Solution of Rational Difference Equations by Applying the Differential Transform Method (Journal of Humanitarian and Applied Sciences, 2020)
In recent years, much consideration has been devoted to the newly developed methods to construct analytic solutions of non-linear difference equations. One of these reliable methods is the Differential Transform Method DTM which has been used extensively to solve different types of linear and non-linear problems. In this paper, we explore the potential of using the DTM to solve rational difference equations and identify new open problems and conjectures of this kind.
Keywords: Rational Difference Equations; Differential Transform Method (DTM)